2011
DOI: 10.1007/s00300-010-0940-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of meio- and macrobenthic standing stocks and diversity in an Arctic fjord (Adventfjorden, Spitsbergen)

Abstract: Strong environmental seasonality is a basic feature of the Arctic system, still there are few published records of the seasonal variability of the Arctic marine biota. This study examined the year-round seasonal changes of soft bottom macro-and meiobenthic standing stocks and diversity on a station located in an Arctic fjord (Adventfjorden, Spitsbergen). The seasonality observed in benthic biota was related to the pelagic processes, primarily the seasonal fluxes of organic and inorganic particles. The highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
(55 reference statements)
2
30
0
1
Order By: Relevance
“…For meiofauna, little response in the abundance was recorded after the sedimentation of the spring phytoplankton at the Alaskan shelf by Fleeger et al (1989) or in a North Water Polynyas by Ambrose and Renaud (1997). On the other hand, Pawłowska et al (2011) reported a clear signal of increased abundance and biomass of meiofauna and macrofauna after the spring bloom at soft-bottom shallow (30 m) station located in Adventfjorden, a small basin influenced by a glacial river inflow. Also, Morata et al (2015) reported that in Rijpfjorden-a fjord located off Nordaustlandet Island (Svalbard Archipelago)-the macrobenthic biomass (at depths below 200 m) was lower in winter (January) than that recorded by previous studies performed in the same locality in summer season (Carroll and Ambrose 2012).…”
Section: Discussion Seasonal Variability In Benthic Communitiesmentioning
confidence: 99%
“…For meiofauna, little response in the abundance was recorded after the sedimentation of the spring phytoplankton at the Alaskan shelf by Fleeger et al (1989) or in a North Water Polynyas by Ambrose and Renaud (1997). On the other hand, Pawłowska et al (2011) reported a clear signal of increased abundance and biomass of meiofauna and macrofauna after the spring bloom at soft-bottom shallow (30 m) station located in Adventfjorden, a small basin influenced by a glacial river inflow. Also, Morata et al (2015) reported that in Rijpfjorden-a fjord located off Nordaustlandet Island (Svalbard Archipelago)-the macrobenthic biomass (at depths below 200 m) was lower in winter (January) than that recorded by previous studies performed in the same locality in summer season (Carroll and Ambrose 2012).…”
Section: Discussion Seasonal Variability In Benthic Communitiesmentioning
confidence: 99%
“…The rivers also bring a lot of suspended terrigenous particles, increasing the turbidity in the water during the melt period. The sedimentation rate of inorganic particles is 60 to 80 g m −2 d −1 (Zaja˛czkowski et al 2010) and as a result the bottom in the fjord consists mainly of silt (Pawłowska et al 2011). In the outer part of Adventfjorden the sedimentation rate of suspended particles is reduced and the sediment is coarser (Zaja˛czkowski 2008).…”
Section: Study Areamentioning
confidence: 92%
“…Its depth is from 70 to 100 m. The air temperature ranges between -15 and ?5°C. The Adventfjorden system is affected by two huge river systems which enter the fjord at the inner part, bringing melt waters from glaciers located kilometres away from the coast (Pawłowska et al 2011).…”
Section: Methodsmentioning
confidence: 99%